Effects of food concentration on the reproductive capacity of the invasive freshwater calanoid copepod Arctodiaptomus dorsalis (Marsh, 1907) in the Philippines. Issue 1 (21st October 2017) - Tordesillas, Dino T; Paredes, Princess M F; Villaruel, Kyle P E; Queneri, Clarisse A A M; Rico, Jennete L; Ban, Syuhei; Papa, Rey D S
Abstract: The relationship between food concentration and reproductive capability has been reported for many copepods. Such information can indirectly provide insight as to how species invade new habitats. Arctodiaptomus dorsalis (Marsh, 1907 ), originally described from the United States, has been found to be present in more than 20 Philippine inland water bodies and has also been documented to prefer eutrophic conditions. By feeding this copepod different concentrations of Chlamydomonas reinhardtii Dangeard, 1888 (4 × 10 3 cells ml –1, 5 × 10 4 cells ml –1, 10 5 cells ml –1, and 2 × 10 5 cells ml –1 ), we investigated the effect of food concentration on different reproductive parameters of A. dorsalis : hatching success (HS), clutch size (CS), latency time (LT), inter-clutch duration (ICD), egg production rate (EPR), and fecundity (F). With increasing food concentration HS varied from 13.64% to 50.74%, and CS from 8.50 to 10.57 eggs clutch –1, but these differences were not statistically significantly. EPR significantly increased with food concentration from 3.00 to 7.54 eggs female –1 d –1, while ICD and LT both significantly decreased from 2.00 to 1.71 d and 1.58 to 0.71 d, respectively. F significantly increased from 3.4 to 59.2 eggs female –1 with increasing food concentration, with a maximum of 104 eggs in nine clutches for one individual. The spawning interval thus became shorter and clutches are produced at higher rates at high food concentrations. The successful invasion of A. dorsalis into the inland waters of the Philippines, therefore, could be attributed to the natural eutrophic conditions of these habitats, which has been further aggravated by anthropogenic nutrient inputs into the ecosystem.